Adipose‐derived stem cells‐conditioned medium improved osteogenic differentiation of induced pluripotent stem cells when grown on polycaprolactone nanofibers. Issue 7 (30th October 2018) - Soleimanifar, Fatemeh; Hosseini, Fatemeh Sadat; Atabati, Hadi; Behdari, Asma; Kabiri, Ladan; Enderami, Seyed Ehsan; Khani, Mohammad‐Mehdi; Ardeshirylajimi, Abdolreza; Saburi, Ehsan
Abstract: Considering that the common osteogenic growth factors cannot be transplanted with stem cells to the patients, many studies are underway to find a replacement for these factors. Recently, it has been determined that mesenchymal stem cell (MSC)‐derived conditioned medium (CM) contains effective factors in the bone formation process. In the current study, the synergistic effect of adipose‐derived MSC's CM, and polycaprolactone (PCL) scaffold was investigated on the osteogenic differentiation potential of human induced pluripotent stem cells (iPSCs). After scaffold fabrication by electrospinning and characterization by scanning electron microscopy, iPSCs proliferation in the presence of CM, PCL, and both was evaluated using 3‐[4, 5‐dimethylthiazol‐2‐yl]‐2, 5 diphenyl tetrazolium bromide. Then, iPSCs osteogenic differentiation was investigated while cultured on tissue culture plate and PCL under CM compared with the osteogenic medium using alizarin red staining, calcium content, alkaline phosphatase activity and gene and protein expression analysis. Proliferation rate of the iPSCs was increased while cultured under CM and its effect was synergistically enhanced by culture on PCL. Evaluation of the osteogenic markers was showed CM alone could induce osteogenic differentiation into the iPSCs and this potential was significantly increased while combined with PCL nanofibrous scaffold. According to the results, it was demonstrated that CM has an osteogenic induction property almost the same of the common osteogenic medium and it can also be used potentially with stem cells when transplant to the patients. CM can also help by prolonging cell survival at the site of the defect as well as accelerating healing process. Abstract : The common osteogenic growth factors cannot be transplanted with stem cells to the patients based on their chemical identity and it also showed that mesenchymal stem cells (MSC)‐conditioned medium (CM) contains effective factors in the bone formation process. The synergistic effect of adipose‐derived MSC's CM and polycaprolactone (PCL) scaffold was investigated on the osteogenic differentiation potential of human induced pluripotent stem cells. It was demonstrated that CM has an osteogenic induction property almost the same of common osteogenic induction medium.